2018
DOI: 10.18632/oncoscience.412
|View full text |Cite
|
Sign up to set email alerts
|

Panobinostat suppresses the mesenchymal phenotype in a novel claudin-low triple negative patient-derived breast cancer model

Abstract: Claudin-low triple negative breast cancer (CL-TNBC) is a clinically aggressive molecular TNBC subtype characterized by a propensity to metastasize, recur and acquire chemoresistance. CL-TNBC has a diverse intra- and extracellular composition and microenvironment, and currently there are no clinically approved targeted therapies. Histone deacetylase inhibitors (HDACi) have been investigated as therapeutic agents targeting invasive TNBC phenotypes. However, further studies are required to evaluate HDAC inhibitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…We have previously shown that DACi suppresses the mesenchymal genes CDH2 , VIM , ZEB1 , and ZEB2 , and increases the epithelial gene CDH1 in TNBC cells [ 34 36 ]. As mentioned previously, these genes were confirmed to be up- or downregulated in our RNA-sequencing analysis of TU-BcX-4IC cells treated with romidepsin compared to DMSO ( Fig 4A ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We have previously shown that DACi suppresses the mesenchymal genes CDH2 , VIM , ZEB1 , and ZEB2 , and increases the epithelial gene CDH1 in TNBC cells [ 34 36 ]. As mentioned previously, these genes were confirmed to be up- or downregulated in our RNA-sequencing analysis of TU-BcX-4IC cells treated with romidepsin compared to DMSO ( Fig 4A ).…”
Section: Resultsmentioning
confidence: 99%
“…EMT is a proposed mechanism for the initiation of metastasis and acquisition of drug resistance in TNBC and MBC; pharmacologic inhibition of this transition is one proposed mechanism to prevent metastasis and resistance. We previously published that DACi reverses the mesenchymal morphology and mesenchymal gene expressions in aggressive TNBC subtypes [35,36]. In this study, the response of MBC to DACi treatment was evaluated.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations